If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (25b + -6) + -6(4b + 1) = -7 Reorder the terms: (-6 + 25b) + -6(4b + 1) = -7 Remove parenthesis around (-6 + 25b) -6 + 25b + -6(4b + 1) = -7 Reorder the terms: -6 + 25b + -6(1 + 4b) = -7 -6 + 25b + (1 * -6 + 4b * -6) = -7 -6 + 25b + (-6 + -24b) = -7 Reorder the terms: -6 + -6 + 25b + -24b = -7 Combine like terms: -6 + -6 = -12 -12 + 25b + -24b = -7 Combine like terms: 25b + -24b = 1b -12 + 1b = -7 Solving -12 + 1b = -7 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 1b = -7 + 12 Combine like terms: -12 + 12 = 0 0 + 1b = -7 + 12 1b = -7 + 12 Combine like terms: -7 + 12 = 5 1b = 5 Divide each side by '1'. b = 5 Simplifying b = 5
| -15(X-3)=-25 | | 2X+2(6Y)=126 | | 0.4t=0.7+0.6t | | 5(4x-8)=-20 | | -2(3x+5)+4-7x=6x-18 | | (3P-4)=-25 | | 2.5x=100-2.5x | | 34five+23five= | | 15+9u-3=16+-2u-7 | | 4a^2-11a=3 | | -2/3w-8/15=-4/5 | | 15+9u-3=16-2u-7 | | tan^2x=0.25 | | 3y-27=-15 | | 13/48+x/2-(2x+1)/6=1 | | h=-16t^2+44t+7 | | 6+-2=y | | (x+14)(x+3)=0 | | -4k+2(5k-6)=-3k-30 | | -4(2x+4)=12x-8 | | 4x=6x-3 | | 3x+2x=85 | | 20-18=200 | | .003x-.2=.01 | | 15p+9-11-p=-2(2p+4)-3(2p-2) | | -4(7-2t)=4(t-1) | | 3y*2+3(4y*2-2)= | | y^2+10y=11 | | -5x-6(2x-2)=-107 | | -8(3x+12)-13=4x+10 | | 2x+9=4(x+6) | | 15x+11x+20=90 |